Meta-analysis of surgical outcome after enucleation versus standard resection for pancreatic neoplasms - Hüttner, Felix; Kössler-Ebs, Julia; Hackert, Thilo; Ulrich, Alexis; Büchler, Markus W.; Diener, Markus K. (The British journal of surgery, 2015)
Background Pancreatic enucleation is a tissue-sparing approach to pancreatic neoplasms and may result in better postoperative pancreatic function than standard pancreatic resection. The objective of this review was to compare the postoperative outcome after pancreatic enucleation versus standard resection. Methods MEDLINE, Embase and the Cochrane Library were searched systematically until February 2015 to identify studies comparing the outcome of enucleation versus standard resection for pancreatic neoplasms. After critical appraisal, meta-analysis was performed and the findings were presented as odds ratios or weighted mean differences with corresponding 95 per cent c.i. Results Twenty-two observational studies (1148 patients) were included. Duration of surgery (P < 0·001), blood loss (P < 0·001), length of hospital stay (P = 0·04), and postoperative endocrine (P < 0·001) and exocrine (P = 0·01) insufficiency were lower after enucleation than after standard resection. Mortality (P = 0·44), overall complications (P = 0·74), reoperation rate (P = 0·93) and delayed gastric emptying (P = 0·15) were not significantly different between the two approaches. The overall rate of postoperative pancreatic fistula (POPF) was higher after enucleation than after standard resection (P < 0·001). However, the raised POPF rate did not result in higher mortality or overall morbidity. Sensitivity analysis of high-volume studies (total of more than 20 enucleations and more than 4 per year) showed that, in specialized centres, enucleation can be performed with no increased risk of POPF (P = 0·12). Conclusion Compared with standard resection, pancreatic enucleation can be performed effectively and with comparable safety in high-volume institutions. Enucleation should be considered instead of standard resection for selected pancreatic neoplasms.
Gesehen am 03.06.2020